CMPK2 of triploid crucian carp is involved in immune defense against bacterial infection. (March 2021) - Feng, Chen; Tang, Yiyang; Liu, Xiaofeng; Zhou, Zejun
Abstract: Cytidine/uridine monophosphate kinase 2 (CMPK2) is a thymidylate kinase and in mammals is known to be involved in mitochondrial DNA (mtDNA) synthesis and antiviral immunity. However, very little is known about the function of CMPK2 in fish. With an aim to elucidate the antimicrobial mechanism of CMPK2 in fish, we in this study examined the function of CMPK2 from triploid crucian carp (3nCmpk2). 3nCmpk2 is 426 residues in length and possesses the conserved thymidylate kinase domain. The deduced amino acid sequence of 3nCmpk2 shares 53.2%–99.1% overall identities with the CMPK2 of several fish species. Quantitative real time RT-PCR (qRT-PCR) analysis showed that 3nCmpk2 expression occurred in multiple tissues and was upregulated by bacterial infection in a time-dependent manner. Recombinant 3nCmpk2 (r3nCmpk2) induced mtDNA synthesis and NLRP3 activation. Overexpression of 3nCmpk2 protects the intestinal barrier and hampers the bacterial colonization in fish tissues. These results provide the first evidence that 3nCmpk2 is involved in host innate immunity and plays a protective role in antimicrobial responses during bacterial infection. Highlights: mRNA expression of 3nCmpk2 was significantly induced by bacterial challenge. 3nCmpk2 induced mtDNA synthesis and NLRP3 activation during Aeromonas hydrophila infection . 3nCmpk2 protects the intestinal barrier and hampers the bacterial colonization in fish tissues.